Transcriptome Analysis Reveal Candidate Genes and Pathways Responses to Lactate Dehydrogenase Inhibition (Oxamate) in Hyperglycemic Human Renal Proximal Epithelial Tubular Cells - Wang, Zhimin; Hao, Dan; Fang, Dong; Yu, Jiating; Wang, Xiao; Qin, Guijun (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) is the leading cause of both chronic kidney disease (CKD) and end-stage renal disease (ESRD). Previous studies showed that oxamate could regulate glycemic homeostasis and impacted mitochondria respiration in a hyperglycemia-dependent manner in the rat proximal tubular cells. To explore the transcriptome gene expression profiling of kidney tissues in human renal proximal epithelial tubular cell line (HK-2), we treated HK-2 cells with high D-glucose (HG) for 7 days before the addition of 40 mM oxamate for a further 24 hours in the presence of HG in this study. Afterwards, we identified 3,884 differentially expressed (DE) genes based on adjusted P-value ≤ 0.05 and investigated gene relationships based on weighted gene co-expression network analysis (WGCNA). After qRT-PCR validations, MAP1LC3A, MAP1LC3B (P-value < 0.01) and BECN1 were found to show relatively higher expression levels in the treated groups than the control groups, while PGC1α (P-value < 0.05) showed the lower expressions. Accordingly, enrichment analyses of GO terms and KEGG pathways showed that several pathways (e.g., lysosome pathway (hsa04142) and p53 signaling pathway (hsa04115)) may be involved in a response of HK-2 cells to oxamate. Moreover, via WGCNA, we identified two modules: both the turquoise and blue modules were enriched in pathways associated with lysosome. However, the p53 signaling pathway was only found using all 3,884 DE genes. Furthermore, the key hub genes IGFBP3 (adjusted P-value = 1.34×10-75 and log2(FC) = 2.64) interacted with 6 up-regulated and 12 down-regulated DE genes in the network that were enriched in the p53 signaling pathway. This is the first study reporting co-expression patterns of a gene network after lactate dehydrogenase inhibition in HK-2 cells. Our results may contribute to our understanding of the underlying molecular mechanism of in vitro reprogramming under hyperglycemic stress that orchestrates the survival and functions of HK-2 cells.